Improving Digital Communication Skills for Members of Pringsewu Police Resort - Nur Aminudin; Tahta Herdian Andika; Zulkifli Zulkifli; Afnan Zalfa Salsabila A; Fahlul Rizki; Arif Alexander Bastian (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2024)
The use of digital technology has become an integral part of everyday life, including in the fields of security and law enforcement such as in the Pringsewu Police Resort. However, challenges in adopting and utilizing digital communication skills are still faced by many members of the Pringsewu Police Resort. Therefore, this community service aims to enhance the digital communication skills of Pringsewu Police Resort members through a series of training sessions. The methods used in this service include observation/interview methods, lecture methods, training methods, and the use of relevant digital resources. The results of this community service are highly effective in providing value in terms of knowledge, understanding, and application of digital communication skills by Pringsewu Police Resort members. They become more proficient in using various platforms and digital tools to communicate effectively, both internally and externally. Furthermore, active participation of members in the training demonstrates a high level of concern and enthusiasm for self-improvement and service to the community. By enhancing the digital communication skills of Pringsewu Police Resort members, it will directly contribute to the positive impact on the effectiveness and efficiency of law enforcement tasks and service to the community. The next step is to maintain continuity and expand the scope of the program to ensure sustainability and maximize the benefits obtained.